2010
DOI: 10.1097/md.0b013e3181f15efc
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy Correlates With Increased Risk for Hip Fracture in the Elderly

Abstract: Few studies have addressed the association between polypharmacy and hip fracture using population data. We conducted a population-based case-control study to investigate whether polypharmacy increases the risk for hip fracture in the elderly. We used insurance claims data from the Taiwan Bureau of National Health Insurance, a universal insurance program with a coverage rate of more than 98% of the population in Taiwan. We identified 2328 elderly patients with newly diagnosed hip fracture during the period 2005… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
196
2
16

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 252 publications
(217 citation statements)
references
References 27 publications
3
196
2
16
Order By: Relevance
“…We found that increasing comorbidity was associated with an increased risk of postoperative humeral shaft fracture after total shoulder arthroplasty and humeral head replacement. This finding is not surprising since higher comorbidity indicates more frailty and use of multiple pharmaceutical agents, both of which may be associated with a higher risk of falls and fractures [20][21][22][23] . A small sample size prevented us from examining individual comorbidities (diabetes, heart disease, etc.)…”
Section: Predictors Of Postoperative Humeral Shaft Periprosthetic Framentioning
confidence: 81%
“…We found that increasing comorbidity was associated with an increased risk of postoperative humeral shaft fracture after total shoulder arthroplasty and humeral head replacement. This finding is not surprising since higher comorbidity indicates more frailty and use of multiple pharmaceutical agents, both of which may be associated with a higher risk of falls and fractures [20][21][22][23] . A small sample size prevented us from examining individual comorbidities (diabetes, heart disease, etc.)…”
Section: Predictors Of Postoperative Humeral Shaft Periprosthetic Framentioning
confidence: 81%
“…36 Multivariate logistic regression analysis revealed that the overall OR of falling among patients using ten or more drugs was 8.42 (95% CI 4.73-15.0) compared with patients who used 0-1 drug per day. 37 Another study also showed particular risk for falling (OR 6.1) in patients taking 10+ drugs. 38 Patients who are taking many different types of medications are high-risk groups, where increased monitoring or tailored drug regimens is necessary.…”
Section: Effects Of Characteristics Of Medication Use On Fall Risk Numentioning
confidence: 99%
“…35 Polypharmacy has been associated with falls, hip fractures, hospitalisations and death. [36][37][38][39] Other burdens of polypharmacy include financial costs, practicalities of taking multiple doses and an increase in the possibility of non-adherence to prescribed medicines. Some of these burdens may be partly due to wellintentioned efforts to follow established evidence.…”
Section: Polypharmacymentioning
confidence: 99%